2023
DOI: 10.3390/plants12142689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium Stress on Carbon Sequestration and Oxygen Release Characteristics in A Landscaping Hyperaccumulator—Lonicera japonica Thunb.

Abstract: The carbon sequestration and oxygen release of landscape plants are dominant ecological service functions, which can play an important role in reducing greenhouse gases, improving the urban heat island effect and achieving carbon peaking and carbon neutrality. In the present study, we are choosing Lonicera japonica Thunb. as a model plant to show the effects of Cd stress on growth, photosynthesis, carbon sequestration and oxygen release characteristics. Under 5 mg kg−1 of Cd treatment, the dry weight of roots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…They also found that photosynthetic carbon uptake responded more strongly to warming than carbon release. Liu [9] studied the carbon sequestration and oxygen release capacity of Lonicera japonica, a common garden plant, and investigated the effects of cadmium stress on the growth, photosynthesis, carbon sequestration, and oxygen release characteristics of Lonicera japonica. Jin [10] studied the carbon sequestration potential of 32 typical tree species in Zhengzhou City.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that photosynthetic carbon uptake responded more strongly to warming than carbon release. Liu [9] studied the carbon sequestration and oxygen release capacity of Lonicera japonica, a common garden plant, and investigated the effects of cadmium stress on the growth, photosynthesis, carbon sequestration, and oxygen release characteristics of Lonicera japonica. Jin [10] studied the carbon sequestration potential of 32 typical tree species in Zhengzhou City.…”
Section: Introductionmentioning
confidence: 99%